Characterization of correlations in two-fermion systems based on measurement induced disturbances - Majtey, Ana P. (2013)
We introduce an approach for the characterization of quantum correlations in two-fermion systems based upon the state disturbances generated by the measurement of “local” observables (that is, quantum observables represented by one-body operators). This approach leads to a concept of quantum correlations in systems of identical fermions different from entanglement.